Higenamine protects neuronal cells from oxygen‐glucose deprivation/reoxygenation‐induced injury. Issue 3 (30th September 2018) - Zhang, Yi; Zhang, Jingjing; Wu, Chuntao; Guo, Sheng; Su, Jing; Zhao, Wendong; Xing, Hongxia
Abstract: Higenamine, a plant‐based alkaloid, exhibits various properties, such as antiapoptotic and antioxidative effects. Previous studies proved that higenamine possesses potential therapeutic effects for ischemia/reperfusion (I/R) injuries. However, the role of higenamine in cerebral I/R injury has not been fully evaluated. Therefore, we aimed to investigate the effect of higenamine on cerebral I/R injury and the potential mechanism. Our data showed that higenamine ameliorated oxygen‐glucose deprivation/reperfusion (OGD/R)‐induced neuronal cells injury. Induction of reactive oxygen species and malonaldehyde production, and the inhibition of superoxide dismutase and glutathione peroxidase activity caused by OGD/R were attenuated by higenamine. In addition, higenamine inhibited the increases in caspase‐3 activity and Bax expression, and inhibited the decrease in Bcl‐2 expression. Furthermore, higenamine elevated the expression levels of p‐Akt, heme oxygenase‐1 (HO‐1) and nuclear factor erythroid 2‐related factor 2 (Nrf2). The inhibitor of PI3K/Akt (LY294002) abolished the protective effects of higenamine on OGD/R‐induced neuronal cells. These findings indicated that higenamine protects neuronal cells against OGD/R‐induced injury by regulating the Akt and Nrf2/HO‐1‐signaling pathways. Collectively, higenamine might be considered as new strategy for the prevention and treatment of cerebral I/R injury. Abstract : Higenamine protects neuronal cells against oxygen‐glucose deprivation/reoxygenation‐induced injury by regulating the Akt and Nrf2/HO‐1‐signaling pathways. Collectively, higenamine might be considered as new strategy for the prevention and treatment of cerebral ischemia/reperfusion injury.